Perlindungan Hukum Terhadap Korban Kekerasan Anak Di Panti Asuhan Darussalam - Putje, Moh. Fazlul Rizky; Kaluku, Julisa Aprilia (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Child abuse usually occurs due to negligence of parents or other caregivers. There are examples of cases that require action in child protection, namely child violence that occurs in orphanages. Based on these problems, the latest research is needed regarding the protection of child violence against orphanage children. This study uses empirical legal research methods. This research shows that children should get protection against violence or anything that can harm or hinder their growth and development in accordance with children's rights. Criminal sanctions for orphanage owners who commit violence against foster children can be given as an effort to protect the law from law enforcement officials against victims. Application of criminal sanctions against orphanage owners who commit violence against their foster children. That is, the perpetrator is subject to a penalty of 10 years in prison, the sentence is still not commensurate with the suffering experienced by the victim.